2021
DOI: 10.3389/fcell.2021.714755
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Amino Acids in the Crosstalk Between Mesenchymal Stromal Cells and Neoplastic Cells in the Hematopoietic Niche

Abstract: Within the bone marrow hematopoietic cells are in close connection with mesenchymal stromal cells (MSCs), which influence the behavior and differentiation of normal or malignant lymphoid and myeloid cells. Altered cell metabolism is a hallmark of cancer, and changes in nutrient pools and fluxes are important components of the bidirectional communication between MSCs and hematological cancer cells. Among nutrients, amino acids play a significant role in cancer progression and chemo-resistance. Moreover, selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Physiologically, high citrate is needed for bone matrix deposition [ 41 ], suggesting that MSCs contribute to bone renewal by providing the citrate in the extracellular environment. Moreover, it has been shown that citrate can be taken up and used as energy source by cancer cells [ 42 , 43 ] suggesting that MSC-derived extracellular citrate could sustain the metabolism of hematological cancer cells in the bone marrow niche as described for other metabolites [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, high citrate is needed for bone matrix deposition [ 41 ], suggesting that MSCs contribute to bone renewal by providing the citrate in the extracellular environment. Moreover, it has been shown that citrate can be taken up and used as energy source by cancer cells [ 42 , 43 ] suggesting that MSC-derived extracellular citrate could sustain the metabolism of hematological cancer cells in the bone marrow niche as described for other metabolites [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…82 Glutaminedepleted tumors not only directly inhibit the function of effector T cells through glutamine deprivation but also release cytokines to reduce the tumor-killing effects in the glutamine-depleted TME (Figure 2). 57,[81][82][83] In non-smallcell lung adenocarcinoma, glutamine deficiency induces the expression and release of interleukin (IL)-6 and IL-8, thereby promoting infiltration of immunosuppressive cells into the TME. 84 There is abundant evidence proving that glutamine depletion leads to an immunosuppressive TME in solid tumors.…”
Section: Glutamine Metabolism and Immunomodulationmentioning
confidence: 99%
“…This observation led to the wide incorporation of L‐asparaginase, which rapidly hydrolyzes plasma asparagine (and at a lower rate glutamine), as a drug in ALL therapy. The metabolic cross‐talk between MSCs and ALL blasts was shown to promote resistance of the leukaemia cells to L‐asparaginase treatment 134,135 . Primary human MSCs from the bone marrow of ALL patients use glutamine produced by ALL blasts to synthetize and excrete asparagine, which in return supports the ALL blasts and protects them from L‐asparaginase.…”
Section: Mesenchymal Cells' Significance In Haematological Malignanciesmentioning
confidence: 99%
“…The metabolic cross‐talk between MSCs and ALL blasts was shown to promote resistance of the leukaemia cells to L‐asparaginase treatment. 134 , 135 Primary human MSCs from the bone marrow of ALL patients use glutamine produced by ALL blasts to synthetize and excrete asparagine, which in return supports the ALL blasts and protects them from L‐asparaginase. Higher expression levels of SNAT5, the exporter of asparagine in MSCs, were reported in ALL patients compared to their normal counterparts.…”
Section: Mesenchymal Cells' Significance In Haematological Malignanciesmentioning
confidence: 99%